Peningkatan Komitmen Kerja melalui Coaching - Shintalya, Shintalya; Yuliansyah, Yuliansyah (Jurnal Ilmiah Psyche, 2018)
Coaching method is an approach of structured conversation process aims to help and guide someone (coachee or client) to improve performance or to find the root of the problem and how to overcome it. Through this particular method enable to help employees to increase their commitment impacted to increasing employee engagement so that employees may independently take the initiative and creative in facing the constraints to achieve optimal performance. In this research, researcher use descriptive action research which divided into 3 stages; Pre-coaching stage, stage of coaching process, and final stage (post coaching). The subjects of the study were three employees consisting of 2 males and 1 female with criteria under the age of 30 years and graduated from full scholarship fellowship program. Methods of data collection in this study are using unstructured observation and interviews using CARE coaching method. Meanwhile, to test the validity of the data, researchers use triangulation of sources and member check. The results showed that the three research subjects working at PT TeL have a good working commitment and the coaching process undertaken were able to explore and generate awareness of work commitment to be better and create employee engagement to the company